1992
DOI: 10.1029/92gl00976
|View full text |Cite
|
Sign up to set email alerts
|

High heat flow anomalies over salt structures on the Texas Continental Slope, Gulf of Mexico

Abstract: We made 74 closely spaced (< 2 km apart) heat flow measurements around and over two salt structures on the Texas continental slope, Gulf of Mexico. The values outlined the shape of the heat flow anomalies over both structures. Based on a preceding high resolution seismic survey, we interpreted these structures to be a cylindrical plug and a salt tongue extending from the crest of a wall‐shaped feeder. The heat flow observations clearly reflect differences between the two features and are consistent with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…Jensen (1983) described high temperatures above salt domes as a result of enhanced heat flow due to the thermal conductivity of salt and surface layers of low conductivity. This implies a possible upward motion of deeper fluids due to convection (Khutorskoi et al, 2009;Nagihara et al, 1992). Fresh water can enter through the same pathways that account for the partial dissolution of the salt dome margins which give rise to density driven thermohaline convection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Jensen (1983) described high temperatures above salt domes as a result of enhanced heat flow due to the thermal conductivity of salt and surface layers of low conductivity. This implies a possible upward motion of deeper fluids due to convection (Khutorskoi et al, 2009;Nagihara et al, 1992). Fresh water can enter through the same pathways that account for the partial dissolution of the salt dome margins which give rise to density driven thermohaline convection.…”
Section: Discussionmentioning
confidence: 98%
“…Salt structures near the surface form geothermal zones (Jensen, 1983;Nagihara et al, 1992) and have an impact on groundwater salinity (Magri et al, 2009). The rise of salt domes provokes faults in the overlying geological strata.…”
Section: Introductionmentioning
confidence: 99%
“…[39] The contrast of conductivity between sediment ($0.8-1 W/m/K) and basalt ($1.5-2.5 W/mK) [Clauser and Huenges, 1995] can potentially contribute to a lateral heat transfer. This heat refraction effect, which has been shown to be important in some specific environments [Nagihara et al, 1992], could generate small wavelength anomalies such as that observed on profile OP or profile CD, where the basement shows a high bounded by two lows. Von Herzen [2004] has discussed some aspect of heat refraction for buried structures in the old ocean crust.…”
Section: A3 Heat Refractionmentioning
confidence: 96%
“…In another study of the Texas continental slope, Nagihara et al (1992) made 74 measurements within ±10% accuracy of heat flows over 2 irregularly shaped salt domes, spacing samples 1-3 m apart. Nagihara et al found that heat flow ranged from 25 to 40 mW/m 2 beyond salt influence, while ranging from 50 to 100 mW/m 2 directly over the salt.…”
Section: Thermal Gradientsmentioning
confidence: 99%